Analisis Keputusan Australia Menjatuhkan Sanksi Kepada Fiji Pasca Kudeta Militer - Honestya, I Putu Bagus; Sushanti, Sukma; Suwecawangsa, Adi P. (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2019)
ABSTRACT This final assignment discusses about Australia's choice to decide the policy to impose sanctions on Fiji after the 2006 military coup. The Australian decision will be analyzed using the Foreign Policy Theory and the Rational Actor Model. The analysis within this final assignment will provide the reasons behind choosing policies to impose sanctions in response to a military coup in Fiji. The Rational Actor model is used to explain that Australia as a rational actor will choose the most strategic policy among various alternatives to achieve its national interests. The outcome of this research is a clear explaination about the reason that motivate Australia chose the option to impose sanctions on Fiji. After considering the costs and benefits of various alternative options available, the option to impose sanctions is the most suitable for Australia in response to the 2006 military coup in Fiji. Keywords : Australia, Fiji, Coup , Sanction